2007
DOI: 10.1111/j.1937-5956.2007.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Suites' Operations Management

Abstract: Surgical suites are a key driver of a hospital's costs, revenues, and utilization of postoperative resources such as beds. This article describes some commonly occurring operations management problems faced by the managers of surgical suites. For three of these problems, the article also provides preliminary models and possible solution approaches. Its goal is to identify open challenges to spur further research by the operations management community on an important class of problems that have not received ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 18 publications
1
125
0
Order By: Relevance
“…For hospitals using block schedules, the literature on surgery scheduling describes the problem as consisting of three stages: (1) determining the amount of OR time to allocate to various surgical specialties, (2) creating a block schedule implementing the desired allocations, and (3) scheduling individual patients into available time (Blake & Donald, 2002;Santibañez, Begen, & Atkins, 2007;Testi, Tanfani, & Torre, 2007). First stage decisions typically reflect the long-term strategic goals of hospital management, such as meeting the demand for surgical specialties' services, achieving desired levels of patient throughput, or maximizing revenue (Blake & Carter, 2002;Gupta, 2007;Santibañez et al, 2007;Testi et al,2007). The second and third stages represent medium-and short-term operational decisions, respectively, but differ markedly in their objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For hospitals using block schedules, the literature on surgery scheduling describes the problem as consisting of three stages: (1) determining the amount of OR time to allocate to various surgical specialties, (2) creating a block schedule implementing the desired allocations, and (3) scheduling individual patients into available time (Blake & Donald, 2002;Santibañez, Begen, & Atkins, 2007;Testi, Tanfani, & Torre, 2007). First stage decisions typically reflect the long-term strategic goals of hospital management, such as meeting the demand for surgical specialties' services, achieving desired levels of patient throughput, or maximizing revenue (Blake & Carter, 2002;Gupta, 2007;Santibañez et al, 2007;Testi et al,2007). The second and third stages represent medium-and short-term operational decisions, respectively, but differ markedly in their objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…OR planning and scheduling have also received considerable attention in scientific literature, as demonstrated by the review of Cardoen, Demeulemeester, and Beliën (2010), which has identified 246 publications, among which 114 in the first decade of the present millennium. Other comprehensive reviews which address OR scheduling are provided by Erdogan et al (2011), Gupta (2007), Gupta and Denton (2008) and Cayirli and Veral (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the surgeon is a very expensive resource, decreasing the surgeon's waiting time has been the subject of many papers , Denton and Gupta, 2003, Gupta, 2007, and Lebowitz, 2003. This factor has to take into consideration the minimum waiting time a surgeon needs between operations (Pause Time).…”
Section: Objective Functionmentioning
confidence: 99%
“…Late starts result in direct costs associated with overtime staffing when the surgery finishes later than the end of the appropriate shift (Kharraja et al, 2006. Gupta, 2007, Fei et al, 2008and Adan and Visser 2002.…”
Section: Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation